Effects of Ridge-Furrow System Combined with Different Degradable Mulching Materials on Soil Water Conservation and Crop Production in Semi-Humid Areas of China - Ren, Xiaolong; Chen, Xiaoli; Cai, Tie; Wei, Ting; Wu, Yang; Ali, Shahzad; Zhang, Peng; Jia, Zhikuan (Frontiers in Plant Science, 2017)
In China, the ridge-furrow water conservation planting (RC) system is advantageous for improving crop yields and rainwater use efficiency. In RC planting system, plastic film-mulched ridges are employed for water harvesting while the furrows serve as infiltration and planting belts. To optimize the RC system and to overcome problems due to the lack of water in semi-humid areas at risk of drought, we mulched the furrows with 8% biodegradable film (RCSB), liquid film (RCSL), or no mulching in the furrows (RCSN), while conventional flat planting (CF) was employed as the control. After four year (2007-2010) consecutive field study, the results showed that the soil water storage level in the 0-100 cm layer with four treatments was ranked as follow: RCSB>RCSL>RCSN>CF, while the RCSB and RCSL were 26.3 and 12.2 mm greater than RCSN, respectively. Compared with CF, the average soil temperature was significantly (P<0.05) higher by 3.1, 1.7, and 1.5 ℃ under the RC planting treatments (RCSB, RCSL, and RCSN) during each year, respectively. The average ET rate of RC treatments were all lower than CF in each experimental year, and the average decreased by 8.0% (P<0.05). The average yields with RCSB, RCSL, and RCSN increased by 2665, 1444, and 1235 kg ha–1, respectively, and the water use efficiency (WUE) increased by 51.6%, 25.6%, and 21.1%, compared with CF. RCSB obtained the highest economic benefit, the average net income was higher than CF by 4020 Yuan ha–1. In conclusion, we found that RC planting with biodegradable film mulching in the furrows is the best cultivation pattern in the semi-humid areas of China in terms of both environmental and economic benefits.